MORFOMETRIK ORGAN DALAM ITIK CIHATEUP YANG DIBERI KITOSAN IRADIASI DALAM RANSUM - Nugraha, Arif; Latipudin, Diding (Jurnal Sains dan Teknologi Industri Peternakan, 2022)
Sixty Cihateup ducks in the grower phase were used in this study to study the effect of adding irradiated chitosan to the morphometrics of proventriculus, ventriculus, intestine, liver and heart. The sample ducks were grouped into two groups, each treated with 150 ppm chitosan in drinking water and without chitosan. The research data were analyzed using the unpaired T-Student test. The results showed that the use of irradiated chitosan, overall reduced the morphometrics of the digestive tract (proventriculus, ventriculus, intestine), as well as the liver and heart. These results indicate the role of chitosan as an inhibitor of lipogenesis so that it inhibits growth by continuous administration.